2007
DOI: 10.1103/physreve.76.051805
|View full text |Cite
|
Sign up to set email alerts
|

Random loop model for long polymers

Abstract: Remarkably little is known about the higher-order folding motifs of the chromatin fibre inside the cell nucleus. Folding depends among others on local gene density and transcriptional activity and plays an important role in gene regulation. Strikingly, at fibre lengths above 5 to 10 Mb the measured mean square distance˙R 2¸b etween any two points on the chromatin fibre is independent of polymer length. We propose a polymer model that can explain this levelling-off by means of random looping. We derive an analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
117
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 25 publications
2
117
0
Order By: Relevance
“…We have shown that loop structures lead to a strong effective repulsion and for a first time quantitatively analyzed the strength of the resulting interactions. Surely, the formation of multiple loops in the system of chromatin which has been proposed in several models 6,20,45,46 induces even stronger effects and therefore might be responsible for maintaining the segregated state of chromosomes found in several experiments 9 . Indeed, studies of looping polymers have revealed an effect on the abundance of inter-chromosomal contacts 12,13 .…”
Section: Discussionmentioning
confidence: 95%
“…We have shown that loop structures lead to a strong effective repulsion and for a first time quantitatively analyzed the strength of the resulting interactions. Surely, the formation of multiple loops in the system of chromatin which has been proposed in several models 6,20,45,46 induces even stronger effects and therefore might be responsible for maintaining the segregated state of chromosomes found in several experiments 9 . Indeed, studies of looping polymers have revealed an effect on the abundance of inter-chromosomal contacts 12,13 .…”
Section: Discussionmentioning
confidence: 95%
“…To gain high elasticity, chromatin may change its viscoelastic properties during interphase in such a way that it can rapidly decondense and then consolidate. This could be effected, e.g., by crosslinks that induce the formation of chromatin loops (Bohn et al 2007;Cremer et al 1996;Lieberman-Aiden et al 2009;Münkel and Langowski 1998). In addition to chromatin, then, one might need to invoke contributions by another, stiffer macromolecular network to account for the high elasticity of the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…There we succeeded in developing a theory for the spatial arrangement of a heterogeneous polymer network in terms of correlations and derived a measure for its "clumpiness" and how this affects macromolecular transport. Simultaneously, this model allowed us to study the effect of loopinduced compartmentalization, a concept that has been discussed for some time (Bohn et al 2007;Cremer et al 1996;Münkel and Langowski 1998), and to compare the simulation results quantitatively with the recent intrachromosomal interaction data measured by Lieberman-Aiden et al (2009). However, the combined effects of chromatin chain mobility, specific chromatin folding, and of crowding by other diffusing macromolecules were not included in our earlier work.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic random loop model. This model uses a linear backbone polymer that dynamically folds and builds loops of all length scales (Bohn et al, 2007;Mateos-Langerak et al, 2009). Here, the scaling exponent  becomes 0, as the length N of the polymer exceeds a certain length (2 Mb).…”
Section: Self-avoiding Walk (Saw)mentioning
confidence: 99%